Personality, Subjective Well-Being of Senior Citizens, and Their Living Arrangements - Agustin, Selvi; Setiono, Vivi; Hartanti (ANIMA Indonesian Psychological Journal, 2010)
It was doubtful that subjective well-being (SWB) of senior citizens who lived together with family was better than those who did not. It was assumed that there was correlation between SWB, personality, and a place where they live. Participants of this study were 30 senior citizens; 10 individuals lived with family, 10 individuals lived alone, and 10 individuals lived in foster home. Data was collected through The Big Five Inventory Personality Test combined with Satisfaction with Life Scale and The Affect Balance Scale. Hypothesis was tested with product moment correlation and one way ANOVA. Results show that only extraversion has a significant correlation with SWB (p < 0.05), and there is not any significant difference on SWB senior citizen based upon where they live (p > 0.05). Extraversion profile contributes 16.2% on SWB. Other factors’ contribution is discussed further. Diragukan bahwa kesejahteraan subjektif (subjective well-being = SWB) pada lansia yang tinggal bersama keluarga lebih baik daripada yang tidak tinggal bersama keluarga. Diduga ada keterkaitan SWB, kepribadian dan tempat tinggal lansia. Partispan penelitian adalah 30 lansia: 10 tinggal bersama keluarga, 10 tinggal sendiri, dan 10 tinggal di panti werdha. Data diperoleh melalui The Big Five Inventory Personality Test dan kombinasi Satisfaction with Life Scale dan The Affect Balance Scale. Pengujian hipotesis dengan korelasi product moment dan one way ANOVA. Hasil menunjukkan hanya profil extraversion berhubungan signifikan dengan SWB (p < .05), serta tidak ada perbedaan SWB lansia berdasarkan tempat tinggalnya (p > .05). Profil extraversion memberikan sumbangan 16.2% terhadap SWB. Dibahas lebih lanjut faktor-faktor lain yang menyumbang SWB